Leibniz on the Epistemic Status of the Mysteries - Bardon, Adrian (Philosophy & theology, 2001)
In this paper, I examine Leibniz’s account of the epistemic status of the Christian Mysteries in his “Preliminary Dissertation on the Conformity of Faith with Reason.” In it, the Mysteries are held to be true, yet also to be beyond human comprehension. This conjunction gives rise to a dilemma: how can the Mysteries be meaningfully asserted if they are unintelligible? To answer this, Leibniz compares them to natural truths, which are demonstrable by God alone. To complicate matters, however, he suggests that certain Mysteries have the status of truths of logic, or of mathematics; this raises a special problem in understanding his view of the epistemic status of such Mysteries for us. I offer a suggestion as to how he may have wanted us to think of the relationship between these Mysteries and our faculty of comprehension. I then employ my conclusions in explaining Leibniz’s answer to Bayle’s skepticism regarding the Mysteries, as well as in explaining his answer to the question as to how belief in the Mysteries can be rationally justified.